The contribution of waste management to GHG emission reduction in urban areas (Case study of Jongkong Landfill, Bangka Tengah Regency, Bangka Belitung Islands Province) - Della, Sevia; Kristanto, Gabriel Andari; Dahlan, Astryd Viandila (Indonesian Journal of Multidisciplinary Science, 2025)
This study aims to evaluate the potential of various waste management scenarios to reduce greenhouse gas (GHG) emissions in urban settings, focusing on the Jongkong landfill in Bangka Tengah Regency, Indonesia. The methodology involved collecting data on waste generation, composition, and current practices from municipal records, categorizing municipal solid waste (MSW) into organic, plastic, and other waste types. Four waste management scenario scenarios were modeled: the Business as Usual (BAU) scenario, which reflected current disposal practices, a Biological Scenario that processed organic waste through anaerobic decomposition to produce biogas, and a thermal scenario that utilized pyrolysis for plastic waste to recover energy. The combined scenario showed the best emission efficiency with the lowest net emission value, which is 10,436.22 kg CO2 eq per year, compared to other scenarios. The biological scenario showed a better net emission than the existing one (17,467,402.15 kg CO2/year), supported by the application of anaerobic digestion (AD) which helps reduce emissions. The thermal scenario also showed good performance by generating net emissions of 2,645,866.25 kg CO2-eq/year, driven by the contribution of pyralysis and the reduction of emissions from open burning and indiscriminate disposal. This study not only enhances understanding of GHG emission reduction strategies but also contributes to the development of tailored waste management policies that can be implemented in similar urban contexts. This novel approach highlights the synergistic benefits of combined waste treatment technologies, offering actionable insights for policymakers and contributing localized data to enhance sustainable waste management practices in Indonesia.